Weird & Wonderful - BENTON, Michael (Discovering Dinosaurs, 2015)
Which Dinosaurs had spikes? How did horn-faced donosaurs live? Why did they look so strange? Explore these and other questions about the oddest and most fantastic creatures of the dinosaur age.